The impact of business process modeling on company efficiency - Ida Hindarsah (Jurnal Ekonomi, 2024)
Business process modeling is a strategic approach that companies use to understand, document and manage their operational processes. This research aims to investigate and analyze the impact of implementing business process modeling on the company's level of efficiency. This research uses a qualitative approach with descriptive methods. The research results show that the application of business process modeling has a positive impact on company efficiency and adaptability. A deep understanding of each step in operations allows identification of inefficiencies, optimization of repetitive tasks, and more effective risk management. Additionally, process modeling helps create better team coordination, improve product and service quality, and support faster and more informed decision making. The research results confirm that investment in business process modeling makes a positive contribution to a company's competitiveness and overall performance in the face of continuously changing business dynamics.